2018
DOI: 10.1101/401919
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ventral tegmental area astrocytes orchestrate avoidance and approach behavior

Abstract: The ventral tegmental area (VTA) is a heterogeneous midbrain structure, containing neurons and astrocytes, that coordinates approach and avoidance behaviors by integrating activity from numerous afferents. Within neuron-astrocyte networks, astrocytes control signals from distinct afferents in a circuit-specific manner, but whether this capacity scales up to drive motivated behavior has been undetermined. Using genetic and optical dissection strategies in vitro and during behavior we report that VTA astrocytes … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…While the size of the imaging plane may influence the ability to observe this effect (407 µm vs. 3 mm), mesoscale imaging averages the neuronal activity of several layers, and a reduction in direct or indirect layer I neuronal activity without a reduction in layer II/III activity could still result in a decreased activation area. Furthermore, since astrocytes are key regulators of neurotransmitter clearance, and astrocytic voltage changes can influence the efficiency of this regulation (Gomez et al., 2019) they could also influence the entrainment of somas. Investigation into these effects may be even more important in the context of temporal patterned stimulation (Brocker et al., 2017), in which different neuronal subtypes can differentially entrain during the pulse bursts likely modulating the excitatory inhibitory balance during the inter‐pulse intervals.…”
Section: Discussionmentioning
confidence: 99%
“…While the size of the imaging plane may influence the ability to observe this effect (407 µm vs. 3 mm), mesoscale imaging averages the neuronal activity of several layers, and a reduction in direct or indirect layer I neuronal activity without a reduction in layer II/III activity could still result in a decreased activation area. Furthermore, since astrocytes are key regulators of neurotransmitter clearance, and astrocytic voltage changes can influence the efficiency of this regulation (Gomez et al., 2019) they could also influence the entrainment of somas. Investigation into these effects may be even more important in the context of temporal patterned stimulation (Brocker et al., 2017), in which different neuronal subtypes can differentially entrain during the pulse bursts likely modulating the excitatory inhibitory balance during the inter‐pulse intervals.…”
Section: Discussionmentioning
confidence: 99%
“…Optogenetic stimulation of astrocytes expressing channel rhodopsin 2, which triggers an increase in cytoplasmic Na + thus modulating glutamate neurotransmission, induced real-time avoidance in mice as assessed by a real-time place preference test. This astroglia-driven pathway ultimately relied upon expression of glutamate transporter GLT-1 (Gomez et al, 2019). These experiments demonstrate that astrocytes can trigger complex behavioural paradigm using astroglia-specific homeostatic mechanisms.…”
Section: Astrocytes and Avoidance Behaviourmentioning
confidence: 82%
“…Moreover, astrocytes can decode interneuron activity and transform inhibitory into excitatory signals, contributing to the novel network properties led by the interneuron‐astrocyte interplay (Perea et al, ). Gomez et al reported that astrocytes in ventral tegmental area tune glutamatergic signaling selectively on local inhibitory neurons to drive a functional circuit for learning and memory using optogenetic strategy (Gomez et al, ). In this section, we focus on reviewing the astrocyte‐involved inhibitory neural network, and discussing potential therapeutic strategies of NDs via optogenetics.…”
Section: Astrocytes Integrate Into Inhibitory Neural Networkmentioning
confidence: 99%